Biomarkers of Microbial Translocation and Macrophage Activation: Association With Progression of Subclinical Atherosclerosis in HIV-1 Infection - Kelesidis, Theodoros; Kendall, Michelle A.; Yang, Otto O.; Hodis, Howard N.; Currier, Judith S. (The Journal of infectious diseases, 2012)
Background. The relationships between soluble CD 14 (sCD14), endotoxin (lipopolysaccharide [LPS]), and progression of atherosclerosis have not been defined in human immunodeficiency virus (HIV) infection. Methods. We retrospectively assessed serum sCD14 and LPS levels of 91 subjects in a prospective 3-year study of carotid artery intima-media thickness (CIMT) (AIDS Clinical Trials Group [ACTG] 5078), where subjects were enrolled as risk factor-controlled triads of HIV-uninfected (n = 36) and HIV-infected individuals with (n = 29) or without (n = 26) protease inhibitor (PI)-based therapy for ≥2 years. The primary end point was the yearly rate of change of CIMT (∆CIMT). Results. In multivariate analysis of the HIV-infected subjects, each 1 μg/mL above the mean of baseline serum sCD14 corresponded to an additional 1.52 μm/y (95% confidence interval, .07-2.98; P= .04) in the ∆CIMT. Every 100 pg/mL above the mean of baseline serum LPS corresponded to an additional 0.49 μm/y (95% confidence interval, .18–. 81; P =. 003) in the ∆CIMT. However, in univariate analysis in the HIV-uninfected group sCD14 (P = .33) and LPS (P = .27) levels were not associated with higher ∆CIMT. HIV infection and PI therapy were not associated with baseline serum LPS and sCD14 levels (P > .1). Conclusions. Our data are among the first to suggest that serum biomarkers of microbial translocation (LPS) and macrophage activation (sCD14) predict subclinical atherosclerosis progression in HIV-infected persons.